On the Power and Limits of Empathy - Camassa, Manuel (Springer Nature, 2024)
This book has two main objectives. The first is to identify and adequately describe the phenomenon of empathy. This essentially means offering a strong, reasoned and accurate description of the phenomenon of empathy in order to capture the essence of the empathic phenomenon and clearly distinguish it from other similar emotional phenomena such as sympathy or compassion The second part focuses on the role that this phenomenon can play on the ethical-moral level. The question is whether empathy is necessary or at least important for morality, and if so, to what extent, in what way and for what reasons. This is an open access book.